HPLC-DAD, ESI-MS/MS, and NMR of Lycopene Isolated From P. guajava L. and Its Biotechnological Applications - Amorim, Adriany G. N. (2019)
Psidium guajava L. have been reported to be a rich source of antioxidant compounds. Its carotenoids have been highlighted by their high antioxidant capacity, which offers several benefits for human health. In this sense, lycopene isomers need to be identified. In this work, the comprehensive chemical characterization, by HPLC‐DAD, MS/MS, and NMR, of lycopene isolated from P. guajava L., antioxidant and antimicrobial activity of lycopene extracts and isolated lycopene are evaluated. The FTIR results reported a structure with Z configuration, confirmed by UV‐Vis, with λmax = 448, 473, and 505 nm for 5‐Z lycopene. Furthermore, MS/MS positive ionization shows one fragment m/z 309 [M‐227]+, relatively abundant for isolated lycopene. Experimental and Theoretical NMR studies revealed that guava may contain 5‐Z lycopene because of the similarity found among the peaks. Lycopene extracts presented higher antioxidant activity than isolated lycopene, from both P. guajava L. and tomato, when measured by ABTS and ORAC (r2 = 0.9995 and r2 = 0.9992, respectively). In addition, lycopene extract shows antibacterial efficacy against E. coli, S. aureus, and L. innocua, presenting MBC values of 20 mg mL−1. These results suggest that lycopene extract have potential applicability for food, cosmetics, and pharmaceutical industry.Practical Applications: Lycopene from P. guajava L. is characterized by HPLCDAD, MS, NMR, FTIR, and X-Ray, presented antioxidant capacity by ORAC and antibacterial efficacy against food pathogens.